Pengaruh E-Service Quality, Online Customer Review dan Sales Promotion Terhadap Minat Beli Ulang - Risky Deni Irawan; R.A. Nurlinda (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study examines and analyzes the effect of E-Service Quality, Online Customer Reviews and Sales Promotion simultaneously and partially on repurchase intention in the Kopi Kenangan application. And knowing the most dominant variable in influencing repurchase intention. The research approach used in this research is quantitative research. The sample selection criteria in this study were those aged 17 and over who had ordered coffee and consumed coffee on the Kopi Kenangan application more than once and were in the Greater Jakarta area. Questionnaires collected as many as 150 respondents, the data is then processed using multiple linear regression method. Based on the results of this analysis, it is known that the variables E-Service Quality, Online Customer Review and Sales Promotion simultaneously have a positive effect on repurchasing interest in the Kopi Kenangan application. Partially, the E-Service Quality, Online Customer Review and Sales Promotion variables have a positive effect on repurchasing interest in the Kopi Kenangan application. Then in the results of the analysis the variable Online Customer Review is the most dominant variable.